Gene and protein expression profiles of JAK-STAT signalling pathway in the developing brain of the Ts1Cje down syndrome mouse model. (2nd September 2019) - Lee, Han-Chung; Md Yusof, Hadri Hadi; Leong, Melody Pui-Yee; Zainal Abidin, Shahidee; Seth, Eryse Amira; Hewitt, Chelsee A.; Vidyadaran, Sharmili; Nordin, Norshariza; Scott, Hamish S.; Cheah, Pike-See; Ling, King-Hwa
Abstract: Aims : The JAK-STAT signalling pathway is one of the key regulators of pro-gliogenesis process during brain development. Down syndrome (DS) individuals, as well as DS mouse models, exhibit an increased number of astrocytes, suggesting an imbalance of neurogenic-to-gliogenic shift attributed to dysregulated JAK-STAT signalling pathway. The gene and protein expression profiles of JAK-STAT pathway members have not been characterised in the DS models. Therefore, we aimed to profile the expression of Jak1, Jak2, Stat1, Stat3 and Stat6 at different stages of brain development in the Ts1Cje mouse model of DS. Methods : Whole brain samples from Ts1Cje and wild-type mice at embryonic day (E)10.5, E15, postnatal day (P)1.5; and embryonic cortex-derived neurospheres were collected for gene and protein expression analysis. Gene expression profiles of three brain regions (cerebral cortex, cerebellum and hippocampus) from Ts1Cje and wild-type mice across four time-points (P1.5, P15, P30 and P84) were also analysed. Results : In the developing mouse brain, none of the Jak / Stat genes were differentially expressed in the Ts1Cje model compared to wild-type mice. However, Western blot analyses indicated that phosphorylated (p)-Jak2, p-Stat3 and p-Stat6 were downregulated in the Ts1Cje model. During the postnatal brain development, Jak / Stat genes showed complex expression patterns, as most of the members were downregulated at different selected time-points. Notably, embryonic cortex-derived neurospheres from Ts1Cje mouse brain expressed lower Stat3 and Stat6 protein compared to the wild-type group. Conclusion : The comprehensive expression profiling of Jak/Stat candidates provides insights on the potential role of the JAK-STAT signalling pathway during abnormal development of the Ts1Cje mouse brains.